Evaluación del poder inhibitorio de las saponinas de dos variedades de agave en la fermentación del aguamiel - Aigaje Quinatoa, Yuddy Erika (2021)
The purpose of this research work was to study the extraction of saponins from two varieties of agave to evaluate their inhibitory power in the fermentation of mead, for which the extraction of saponins was developed through the maceration method using the interaction of the fine powder of the leaves of Agave americana L and Furcraea andina) with a combination of solvents (water-ethanol) for 72 hours, for which a factorial arrangement of AxB was performed under a randomized complete block design (DBCA), whose response variable was the foam index, in this way the four treatments with the highest amount of foam were determined, which were analyzed in the Laboratorio Multianalítyca SA by the method of high efficiency liquid chromatography to determine the concentration of the saponins and the following data was obtained: corresponding t1 (fine powder of Agave americana L + the solvent 100% water) with 0.21%, t2 (fine powder of Agave americana L + solvent 75% water-25% ethanol) with 0.14%, t6 (fine powder of Furcraea andina + solvent 100% water) with 0.22% and t8 (fine powder of Furcraea andina + solvent 50% water-50% ethanol) with 0.16%; After this, 0.05ml of the saponins from the four treatments was taken and added to 400ml of mead, in addition, a sample called standard was selected to evaluate the inhibition in the fermentation of the mead considering the following parameters: physical-chemical (°Brix, alcoholic degrees and pH); where the best treatment t6 was determined, corresponding to (Andean Furcraea fine powder + 100% water) with the following results: 9.7° Brix, 5.9 alcoholic degrees and 6.8 pH. The mead with the addition of the saponins was subjected to a physical-chemical analysis: pH 4, 11.75 °Brix, 0.26GL; nutritional analysis: 0.01% fat, <0.01mg/100g cholesterol, 70.17mg/kg sodium, 5.38% total solids, 0.30% protein and microbiological analysis with total count <10UFC/cm3, E. Coli 1.7x102 UFC/cm3, molds <10 UFC/cm3 and yeasts 3.2x10 4 UFC/cm3. The best extraction treatment was t6, which corresponds to (Andean Furcraea fine powder + 100% water) with a concentration of 0.22% of saponins and which in turn, when mixing in the mead, it was possible to identify that there was a slight inhibition in the fermentation process since the physical and chemical parameters remained almost similar to the initial conditions, this due to the destructive action of the saponins on the yeasts, reducing their concentration and therefore increasing the fermentation time of the mead.